2022
DOI: 10.1007/s12603-022-1845-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional Decline in COVID-19 Older Survivors Compared to Other Pneumonia Patients, a Case Control Study

Abstract: Objectives Among patients over 75 years, little is known about functional decline due to COVID-19. The aim of this study was to explore this functional decline, compare to other infectious pneumonia. Design and Setting This case-control study included all COVID-19 patients hospitalized from March to December 2020 in Acute Geriatric Ward in Nantes University Hospital matched 1/1 with patients with pneumonia hospitalized in geriatric department between March 2017 and Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…In our study, half of the patients experienced a functional decrease of at least 5 Barthel Index (BI) points, a third showed a clinically relevant decrease of at least 10 points, and one in ten had a catastrophic decrease of 30 or more points. The functional decline in our patients was higher than the one in five at 30 days previously reported in similar pre-COVID-19 studies [21,22], but it is in line with the results of the study by Le Gentil et al, who reported a 3-month persistent functional decline of 42% in older adults admitted for pneumonia in 2020 [23]. Moreover, consistent with these observations and those of other authors, we did not find that COVID-19 etiology was a statistically significant independent factor for functional decline, while age [23], previous institutionalization and a better score in BI [24], Charlson Index (CCI) [24], and length of stay [23,24] were risk factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, half of the patients experienced a functional decrease of at least 5 Barthel Index (BI) points, a third showed a clinically relevant decrease of at least 10 points, and one in ten had a catastrophic decrease of 30 or more points. The functional decline in our patients was higher than the one in five at 30 days previously reported in similar pre-COVID-19 studies [21,22], but it is in line with the results of the study by Le Gentil et al, who reported a 3-month persistent functional decline of 42% in older adults admitted for pneumonia in 2020 [23]. Moreover, consistent with these observations and those of other authors, we did not find that COVID-19 etiology was a statistically significant independent factor for functional decline, while age [23], previous institutionalization and a better score in BI [24], Charlson Index (CCI) [24], and length of stay [23,24] were risk factors.…”
Section: Discussionsupporting
confidence: 93%
“…The functional decline in our patients was higher than the one in five at 30 days previously reported in similar pre-COVID-19 studies [21,22], but it is in line with the results of the study by Le Gentil et al, who reported a 3-month persistent functional decline of 42% in older adults admitted for pneumonia in 2020 [23]. Moreover, consistent with these observations and those of other authors, we did not find that COVID-19 etiology was a statistically significant independent factor for functional decline, while age [23], previous institutionalization and a better score in BI [24], Charlson Index (CCI) [24], and length of stay [23,24] were risk factors. We consider that restrictions due to pandemic lockdowns-such as isolation, limited mobility, and little physical therapy-contributed to greater functional decline even in patients with a higher BI.…”
Section: Discussionsupporting
confidence: 93%
“…Another cause of variation could be due to modifications in the scales for functional status measurement, which in some studies has been evaluated with the Katz BADL scale, 29 and in others, with a simplified IADL scale, such as the modified Lawton Index. [15][16][17]30 As for the burden of comorbidity, another analysis found that stroke and depression were predictors of functional decline. 15 Furthermore, it has been documented that various diseases significantly increased mortality during COVID-19, including CKD (RR = 3.9), dementia (RR = 3.6), cardiovascular diseases (OR = 2.4) and diabetes mellitus (OR = 1.7).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few investigations on the subject, older people have been shown to suffer complications, functional decline and quality of life decrease. [14][15][16][17][18] The cause of this functional decline is multifactorial. Inflammation has been proposed to play an important role, and a positive correlation has been identified between elevated levels of inflammatory markers such as C-reactive protein, IL-6 and D-dimer and loss of muscle strength, 19 functional limitation 20 and disability.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque existen pocas investigaciones al respecto, se ha demostrado que las personas mayores sufren complicaciones, deterioro funcional y disminución de la calidad de vida. [14][15][16][17][18] La causa de este deterioro funcional es multifactorial. Se ha propuesto que la inflamación desempeña un papel importante y se ha identificado una correlación positiva entre niveles elevados de marcadores inflamatorios como la proteína C reactiva, IL-6 y el dímero D con pérdida de fuerza muscular, 19 limitación funcional 20 y discapacidad.…”
Section: Antecedentesunclassified